PENGGUNAAN SISTEM KOMPUTERISASI PADA KINERJA PROCUREMENT DEPARTMENT DI GOLD BRIDGE SHIPPING LTD - Fiasinta Fiasinta; Sri Purwantini (Politeknik Ilmu Pelayaran Semarang, 2019)
ABSTRACT Indonesia challenges several developed countries with sophisticated and structured technological systems, which are influencing technology in Indonesia. Likewise a company company is a lot of assets important and must be ordered properly processed appropriately needed system usage computerized. In the era of excellent service, Gold Bridge Shipping Ltd must provide fast service, open, and professional for invited partners. Therefore, the purchasing process must be use information technology so that the service process is carried out systematically. However The computerized system has not been fully implemented in the Procurement Department so Stop the activities in the Procurement department. This research The Department of Performance Procurement uses and does not use a computerized system. Method the research used is descriptive qualitative. The data source used is library research, interview and documentation. Results of this research the use of computerized systems according to computer specifications that have not been updated, system interruption computers, database system management, computer component damage, and lack of human resources